Evaluación de las propiedades acústicas de diferentes muestras de un material no tejido de fibras naturales compuestas de un gran porcentaje de musaceae - Argotti Gómez, Marcelo Alejandro (2017)
This study determines the calculation process and measurement of sound absorption coefficients of a nonwoven material of natural fibers; compound of a high percentage of musaceae. The study was developed in three main stages, being: the physical determination, the measurement of the absorption coefficients of the samples in the impedance tube and the generation of reports on the basis of the data obtained. The measurements were carried out on the basis of the standards UNE EN ISO 10534-2 “Determination of the acoustic absorption coefficient and acoustic impedance in impedance tubes”, second part, “Method of the transfer function”, which establishes the guidelines for providing reliably measurements and information about the absorption coefficient of a material in study. Subsequently, the musaceae samples were analyzed based on the ASTM E 2611-09 normative, under the name of “Standard Test Method for Measurement of Normal Incidence Sound Transmission of Acoustical Materials Based on the Transfer Matrix Method”, in order to obtain the transmission loss (TL). The measurements, their respective results and the difficulties that occurred during the investigation, are discussed and analyzed with the aim of estimating the possible assembly of the musaceae material in the field of acoustic conditioning.